2014
DOI: 10.7554/elife.01977
|View full text |Cite
|
Sign up to set email alerts
|

miR-142 regulates the tumorigenicity of human breast cancer stem cells through the canonical WNT signaling pathway

Abstract: MicroRNAs (miRNAs) are important regulators of stem and progenitor cell functions. We previously reported that miR-142 and miR-150 are upregulated in human breast cancer stem cells (BCSCs) as compared to the non-tumorigenic breast cancer cells. In this study, we report that miR-142 efficiently recruits the APC mRNA to an RNA-induced silencing complex, activates the canonical WNT signaling pathway in an APC-suppression dependent manner, and activates the expression of miR-150. Enforced expression of miR-142 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
133
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(143 citation statements)
references
References 67 publications
(103 reference statements)
8
133
2
Order By: Relevance
“…miRNAs target numerous genes, including HIF, mTOR, VEGF and VHL, through translational inhibition or the induction of mRNA degradation, which suggests that miRNAs function as important factors in RCC initiation and development (36,37). Previous studies have reported that miR-142-3p is dysregulated in various types of cancer (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), and may therefore function as a biomarker. The expression of miR-142-3p in RCC has not yet been validated by qPCR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNAs target numerous genes, including HIF, mTOR, VEGF and VHL, through translational inhibition or the induction of mRNA degradation, which suggests that miRNAs function as important factors in RCC initiation and development (36,37). Previous studies have reported that miR-142-3p is dysregulated in various types of cancer (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), and may therefore function as a biomarker. The expression of miR-142-3p in RCC has not yet been validated by qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in breast cancer, overexpressed miR-142-3p regulates the properties of breast cancer stem cells (BCSCs), at least in part by activating the WNT signaling pathway and miR-150 expression. Previous in vivo experiments demonstrated that the enforced expression of miR-142 in normal mouse mammary stem cells resulted in the regeneration of hyperproliferative mammary glands, whilst the knockdown of endogenous miR-142 effectively suppressed organoid formation by BCSCs, and also slowed tumor growth initiated by human BCSCs (22). Downregulation of miR-142-3p in thyroid neoplastic tissues contributes to thyroid follicular tumorigenesis through the targeting of ASH1L and MLL1, and subsequently promotes its tumor suppressive function (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-142 are upregulated in human breast cancer stem cells. And knockdown of miR-142 significantly suppressed organoid formation and slowed tumor growth in vivo [5].…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-one miRNAs were differentially expressed between the non-pCR and pCR groups in the analysis of all 40 patients with HER2-positive breast cancer (Table III). Nine of these 21 miRNAs are reported to be associated with breast cancer (17)(18)(19)(20)(21)(22)(23)(24)(25). The other 12 miRNAs have no reported correlation with breast cancer.…”
Section: Resultsmentioning
confidence: 99%